Halal Standards as Elementsi n the Legal Framework of 3d/4d-printed Food Using Source-composition-manufacturing and Halal Forensic Concepts - Baharuddin, A.S.; Ismail, W.A.F.W.; Lukman, A.M.; Ghazali, M.I.M.; Alauddin, M.S.; Shaarani, S.M.; Wan Harun, M.A.; Tuan Ibrahim, T.M.F.H. (Rynnye Lyan Resources, 2024)
Indexed by Scopus/MyCite